FIGURE 1 in Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura) - Ahyong, Shane T.; Dawson, Elliot W. (Zenodo, 2006)
FIGURE 1. Neolithodes yaldwyni sp. nov., male holotype (cl 141.5 mm, cw 124.1 mm, NIWA 3434). A, overall dorsal view. B, carapace, dorsal view. C, anterior carapace, right lateral view. Published as part of Ahyong, Shane T. & Dawson, Elliot W., 2006, Lithodidae from the Ross Sea, Antarctica, with descriptions of two new species (Crustacea: Decapoda: Anomura), pp. 45-68 in Zootaxa 1303 on page 48, DOI: 10.5281/zenodo.173679